2022
DOI: 10.3390/sports10060081
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Approaches to Talent Identification in Team Sports: A Narrative Review

Abstract: Talent identification (TID) and talent development (TD) continue to receive significant investment from team sports organisations, highlighting their importance in attempting to identify potential elite athletes. Accompanying this continual pursuit to unearth future talent is an ever-increasing body of research aiming to provide solutions and strategies to optimise TID and TD processes. Therefore, the aim of this review is to provide a summary and critical synthesis of the methodological approaches applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 87 publications
0
16
1
Order By: Relevance
“…Our reported AUC is much higher compared to the reported AUC that ranged from 0.65 to 0.79 when general motor performance (i.e., 40 m sprint, agility, CMJ, Yo-Yo intermittent recovery test) and domain-specific motor performance parameters were used as predictors of future U17 players’ status [ 38 ]. The difference in the age groups and the associated maturity levels between the forementioned study and the present study may be the reason we reported higher AUC, since both age and maturity have a significant impact on prediction models [ 15 , 29 , 39 , 88 , 89 ].…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…Our reported AUC is much higher compared to the reported AUC that ranged from 0.65 to 0.79 when general motor performance (i.e., 40 m sprint, agility, CMJ, Yo-Yo intermittent recovery test) and domain-specific motor performance parameters were used as predictors of future U17 players’ status [ 38 ]. The difference in the age groups and the associated maturity levels between the forementioned study and the present study may be the reason we reported higher AUC, since both age and maturity have a significant impact on prediction models [ 15 , 29 , 39 , 88 , 89 ].…”
Section: Discussioncontrasting
confidence: 48%
“…On the other hand, soccer clubs are businesses that want to capitalize on their assets as soon as they can and prolong their players’ career to maximize the potential revenue [ 4 , 11 , 12 , 13 ]. Therefore, soccer clubs have invested in early talent identification programs, as early as 11 to 16 years old, to develop these youth players into elite-professional ones [ 4 , 10 , 13 , 14 , 15 ]. Williams and Reilly [ 16 ] have developed the “Potential Predictors of Talent in Soccer”, which incorporates 25 potential predictors in relation to physical, physiological, psychological, and sociological components [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has significant implications for both practice and research. Research has long acknowledged the range of complex biopsychosocial factors that influence TD (Abbott and Collins, 2004 ), mostly ending the reductionistic search for single variables causative of elite performance (Barraclough et al, 2022 ). We suggest that research at the system level should follow, recognizing the inherent complexity, perhaps utilizing mixed methods at multiple levels of analysis (Headley and Plano Clark, 2020 ).…”
Section: Leading Talent Systemsmentioning
confidence: 99%